Dari Keadilan Raja Kepada Undang-Undang Agama: Perkembangan Semasa Islam di Brunei: From Royal Justice to Religious Law: The Current Development of Islam in Brunei - Ismail, Siti Zubaidah; Awang Haji Amai, Norasiah (Journal of Al-Tamaddun, 2023)
When Islam was accepted as the religion of the nation, embraced by the royal and their subjects, a new country was born and emerged as the Kesultanan Melayu Islam (Islamic Malay Sultanate) and known in the present day as Brunei Darussalam. The Brunei monarchy made the Islamic teachings and tenets as the basis to form the state law and remains so until now, despite the fact that it used to be referred to personal law by the colonial power during the British era in Borneo. Scholars have been focusing on the history and development of Islamic law in Brunei but rarely discuss on the history of criminal legislation, particularly on the development of shariah criminal offences. As such, this article discusses that aspect in order to examine the history and the development of what is known today as shariah criminal offences in Brunei in light of the Perintah Kanun Hukuman Jenayah Syariah 2013. To this end, this article contributes significantly in the area of the Islamic legal history in Brunei by exposing the importance of the Sultans in empowering Islamic law in the country as a whole.